AN ANALYTICAL STUDY ON THE INTERSECTION OF RELIGIOUS FREEDOM AND EDUCATION IN INDIA - Prof. (Dr.) Namita Vyas Joshi; Ms. Harmandeep Kaur; Ms. Ravina Parihar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This analytical study examines the complex intersection of religious freedom and education in India, a nation characterized by its rich religious diversity and a constitutional commitment to secularism. The research delves into how the Indian legal framework balances the right to religious freedom, as enshrined in Article 25 of the Constitution, with the state’s mandate to provide universal education, encapsulated in Article 21A. The paper explores key issues such as the role of religious instruction in schools, the rights of religious minorities to establish and administer educational institutions, and the tensions arising from the implementation of secular education policies in a religiously pluralistic society. Through a comprehensive review of judicial interpretations, legislative measures, and policy developments, the study highlights the ongoing challenges in harmonizing religious freedoms with educational objectives. Notable cases, such as the Supreme Court’s judgments on the right to wear religious symbols in educational institutions and the autonomy of minority educational institutions, are critically analysed to understand their implications on the broader discourse of religious freedom and education. The research also addresses contemporary debates on the inclusion of religious education in public schools, the impact of government regulations on the operation of religious schools, and the efforts to promote educational inclusivity while respecting religious sensitivities. By evaluating the effectiveness of existing policies and suggesting possible reforms, this study aims to contribute to the discourse on ensuring equitable and inclusive education that respects religious diversity in India. The findings underscore the need for a nuanced approach that upholds constitutional values and promotes harmonious coexistence in India’s multicultural educational landscape.